The moderating effect of host country co-workers' citizenship behaviour on expatriate adjustment and contextual performance of expatriates in Malaysia - Zakariya, Noor Hafiza; Othman, Abdul Kadir; Abdullah, Zaini (2017)
Despite today’s international business environment challenges, international assignments remain a crucial aspect as a global strategy of multinational corporations (MNCs).MNCs tend to expand their international business to host countries by implementing expatriation practices. As the expatriation emerges, the issue of expatriates’ job performance remains as a central concern among human resource professional, scholars and practitioners as well as multinational organizations.The review of literature indicates that expatriate adjustment always correlates with expatriates’ job performance.Expatriates will succeed in their job, due to the higher level of adjustment in the host country.Several factors may influence this relationship and some studies have focused on the host country national role.But, most expatriate-related research has neglected other expatriate stakeholders such as HCNs.Therefore, role of host country nationals (HCNs) should not be simply ignored by researchers due to its importance. Therefore, this study examines the role of host country co-workers citizenship behavior as a moderator on the relationship between expatriate adjustment and contextual performance.Based on sample of 139 expatriates residing and working in Malaysia, the host country co-workers citizenship behavior was found to be a significant moderator between interaction adjustment and contextual performance.The findings suggest that success of expatriates’ contextual performance does not entirely rest on expatriates’ ability but also the assistance and courteous behavior that they receive during their assignment from host country co-workers.The findings of this study would expand the body of knowledge in expatriate research area especially in international human resource management and cross-cultural management. Furthermore, this study is relevant to human resource professionals, multinational organizations and expatriating firms in making rational decisions when handling international assignment to ensure the success of international assignments among their expatriates.